A master of all trades – linking retinoids to different signalling pathways through the multi-purpose receptor STRA6 - Vinesh Dhokia (Nature Publishing Group, 2021)
Abstract Retinoids are a group of vitamin A-related chemicals that are essential to chordate mammals. They regulate a number of basic processes, including embryogenesis and vision. From ingestion to metabolism and the subsequent cellular effects, retinoid levels are tightly regulated in the organism to prevent toxicity. One component of this network, the membrane receptor STRA6, has been shown to be essential in facilitating the cellular entry and exit of retinol. However, recent data suggests that STRA6 may not function merely as a retinoid transporter but also act as a complex signalling hub in its own right, being able to affect cell fate through the integration of retinoid signalling with other key pathways, such as those involving p53, JAK/STAT, Wnt/β catenin and calcium. This may open new therapeutic strategies in diseases like cancer, where these pathways are often compromised. Here, we look at the growing evidence regarding the novel roles of STRA6 beyond its well characterized classic functions.